Designing a Magnetic Field Practicum Tool on Arduino Uno-Based Toroid-Solenoid Material Using a Hall Effect Sensor - Anisa Septi Pratiwi Pratiwi; Pria Nur Wulandari; Putri Wihatma Andianti; Adisty Pyrenia; Lailiyatul Mukarromah; Alex Harijanto; Subiki (Universitas Nusa Putra, 2023)
Practicum tools are learning media that can increase students' interest and motivation to learn. The practicum tool itself is very effective and efficient in supporting physics learning. The magnetic field is related to electricity and magnetism because the magnetic field is generated by an electric current, there is a transfer of charge because the magnet creates a magnetic field around the magnetic charge. Hall effect sensors are used to measure magnetic fields. The purpose of this research is to assist students in understanding magnetism material and also to fulfill the availability of practicum tools in schools, especially SMA/MA. This research uses a type of quantitative descriptive research. The measurement results in the experiment are whether there is a magnet or not, that is, if the solenoid is brought closer, the LED light will turn on, which means there is a magnet and vice versa, if the solenoid is kept away, the LED light turns off, which means there is no magnetic field. In the experiment, the effect of the number of turns shows that the more the number of turns, the greater the magnetic field. The third experiment is the effect of current with 3 experiments with different current values and the same number of turns, the result is that the greater the current, the greater the magnetic field value. This shows that the results are appropriate and valid and can be used as a physics practicum tool.